Age and weight at puberty in tropical dairy criollo heifers with and without supplementary feeding - Severino-Lendechy, Víctor Hugo; Montiel-Palacios, Felipe; Pérez-Hernández, Ponciano (Ecosistemas y Recursos Agropecuarios, 2017)
The e ect of supplementary feeding on age and weight at puberty was evaluated in 79 pre-pubertal Tropical Dairy Criollo (TDC) heifers of 8 and 10 months of age, distributed in four treatments: T1 and T2) 8 month old heifers with and without supplementary feeding (WSF, n= 20) and (NSF, n= 20), respectively; T3 and T4) 10 month old heifers (WSF, n= 20) and (NSF, n= 19). Average age and weight at puberty in T2 and T4 was 20.4 ± 0.5 months and 287.2 ± 5.9 kg compared with 17.5 ± 0.6 months and 296.8 ± 7.8 kg in T1 and T3 (p < 0.05). The number, follicular diameter (mm) and concentration of progesterone (ng mL−1) in blood was higher (p < 0.05) in T1 and T3 compared to T2 and T4. Supplementary feeding decreases the age at puberty, increases weight gain, improves follicular development and increases blood progesterone concentration in TDC females.